Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Bagian Produksi pada PT Tunas Jaya Packindo Jakarta Barat - Oktaviani, Afrina; Mawarny, Endah (LAP4B, 2024)
The research aims to determine the simultaneous significant impact of Training and Work Discipline on Employee Performance at PT. Tunas Jaya Packindo in West Jakarta. The research methodology employed is quantitative. The population in the study consists of 75 respondents, and a saturated sample technique is used for sample selection. Data collection is carried out using a questionnaire. The analysis techniques include validity testing, reliability testing, normality testing, multicollinearity testing, autocorrelation testing, heteroskedasticity testing, multiple linear regression testing, correlation coefficient testing, determination coefficient testing, t-test, and f-test. The research results indicate that Training has a positive and significant influence on employee performance, and similarly, Work Discipline has a positive and significant impact on employee performance. Simultaneously, there is a positive and significant influence between Training and Work Discipline on employee performance at PT Tunas Jaya Packindo in West Jakarta.